Electrochemical biosensors: a nexus for precision medicine. Issue 1 (January 2021) - Pollard, Thomas D.; Ong, Jun Jie; Goyanes, Alvaro; Orlu, Mine; Gaisford, Simon; Elbadawi, Mohammed; Basit, Abdul W.
Highlights: TDM has the capacity to transform healthcare but lacks suitable portable equipment. ECBs can enable on-site TDM with the potential for fast, cheap, simple measurements. Recent develops include microneedle analysis and closed-loop continuous monitoring. Further work is needed to improve sensor robustness and accuracy. ECBs are poised to usher in the era of digital healthcare and precision medicine. Abstract : Precision medicine is a field with huge potential for improving a patient's quality of life, wherein therapeutic drug monitoring (TDM) can provide actionable insights. More importantly, incorrect drug dose is a common contributor to medical errors. However, current TDM practice is time-consuming and expensive, and requires specialised technicians. One solution is to use electrochemical biosensors (ECBs), which are inexpensive, portable, and highly sensitive. In this review, we explore the potential for ECBs as a technology for on-demand drug monitoring, including microneedles, continuous monitoring, synthetic biorecognition elements, and multi-material electrodes. We also highlight emerging strategies to achieve continuous drug monitoring, and conclude by appraising recent developments and providing an outlook for the field. Teaser: Electrochemical biosensors are cheap, rapid, portable and sensitive, rendering them ideal for point-of-care drug monitoring.